Characterization of TiO2 NPs in Radish (Raphanus sativus L.) by Single-Particle ICP-QQQ-MS - Wojcieszek, Justyna; Jiménez-Lamana, Javier; Ruzik, Lena; Asztemborska, Monika; Jarosz, Maciej; Szpunar, Joanna (Frontiers in Environmental Science, 2020)
Titanium dioxide nanoparticles (TiO2 NPs) are increasingly used in a wide range of consumer products and industrial applications, causing their presence in the environment, where they can interact with plants including edible ones. In addition, the released TiO2 NPs can undergo chemical and physical transformations which may influence their potential toxicity. However, the study of TiO2 NPs in environmental samples by the technique offering the highest sensitivity, ICP-MS, is hampered by the presence of some elements (such as, e.g., Ca abundant in plant tissues) that cause polyatomic and/or isobaric interferences. This study proposed, for the first time, the use of a triple quadrupole ICP operating in tandem mass spectrometry and single particle mode (SP-ICP-QQQ-MS) to study the uptake, translocation and possible transformations of TiO2 NPs with two different nominal sizes in a model plant (Raphanus sativus L.). A careful optimization of the reaction cell conditions (O2 and H2 gas flows) allowed the reduction of background level and resulted in a significant increase of the sensitivity of the analysis, bringing size detection limits for TiO2 NPs down to 15 nm in ultrapure water and to 21 nm in a matrix containing 50 mg L-1 of Ca. In addition, an enzymatic digestion procedure was applied in order to extract intact nanoparticles from the tissues of plants treated with TiO2 NPs, followed by size characterization by SP-ICP-MS. The size distributions obtained in roots treated with TiO2 NPs suggested a preferential uptake of smaller nanoparticles. Results also revealed that the majority of TiO2 NPs were retained in roots. Additionally, no significant dissolution was observed, as well as no differences for nanoparticles found in roots and leaves, proving that radish is able to translocate intact TiO2 NPs up to above ground organs.